Una historia de la UAM: sus primeros 25 años - López Zárate, Romualdo; Casillas Alvarado, Miguel Ángel; González Cuevas, Oscar Manuel (Universidad Autónoma Metropolitana, 2014)
2 archivos PDF (2 volúmenes: 633 páginas)